PENGARUH PERMAINAN BISIK BERANTAI TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 4-5 TAHUN DI TK PERMATA HATI AISYIYAH KOTA TASIKMALAYA - Ani Nursopa; Elfan Fanhas Fatwa Khomaeny; Nita Anggi Purnama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Listening skills are one of the fundamental abilities that need to be developed from an early age, as they play an essential role in understanding information, communicating effectively, and supporting children's language development. The problem underlying this study was that the listening skills of children aged 4–5 years at TK Permata Hati Aisyiyah, Tasikmalaya City, had not yet developed optimally. This study aimed to determine the effect of the Whisper Chain Game on the listening skills of children aged 4–5 years. The study employed a quantitative method using a pre-experimental approach with a one-group pretest–posttest design. The research sample consisted of 23 children aged 4–5 years. Data were collected through observation and documentation and were analyzed using a paired-samples t-test with IBM SPSS Statistics version 27. The results showed that the mean pretest score of 7.3913 increased to 7.6522 in the posttest after the implementation of the Whisper Chain Game. However, the paired-samples t-test revealed a significance value (Sig. 2-tailed) of 0.342 (>0.05), indicating that H₀ was accepted and Hₐ was rejected. Therefore, the Whisper Chain Game did not have a statistically significant effect on the listening skills of children aged 4–5 years. Nevertheless, during the intervention, the children demonstrated progress in understanding the sequence of the game, following instructions, and answering questions related to the conveyed messages. Therefore, the Whisper Chain Game can still be considered an alternative learning activity to stimulate children's listening skills when implemented in an engaging, varied, and continuous manner.